The role of knowledge management for education in Nigeria - J. IKENWE, Ogagaoghene U. IDHALAMA, Christopher A. OMIGIE, Iguehi (International Multidisciplinary Research Journal, 2019)
The study investigates the pivotal role of knowledge management within the academic parlance which has a positive spiral and multiplier effects in a given economy by way of taking our dear country from the shackles of hunger, poverty, insecurity etc. It is clear that the effectiveness and efficiency of any organization/economy rest squarely on its level of knowledge: tacit and explicit. However, this knowledge must be critically studied, tapped, stored and disseminated. This study therefore looked at the concept of knowledge, management, its relevance and role in effective academic system and how knowledge management could contribute in taking a country like Nigeria out of the woods.